Achieving responsible medicines use at practice and farm level. Issue 3 (2nd March 2017) - Tisdall, David A.; Reyher, Kristen K.; Barrett, David C.
Abstract : Medicines use in farm animals and the potential for antimicrobial resistance development and transfer to humans is of increasing scientific, public and political concern. Veterinary surgeons must take the lead in driving change: challenging the currently accepted norms of prescribing and administration, advocating and adopting an evidence‐based approach to therapeutic decision making, and monitoring patterns of medicines use to identify opportunities for intervention and measure impact, while at the same time partnering with farmers to improve herd health management. This article discusses how such a multifaceted, collaborative approach, which involves the whole practice team working in partnership with farm staff, can be highly successful in achieving and sustaining more responsible medicines use on farm and improving animal health.